Terebellomorph polychaetes from hydrothermal vents and cold seeps with the description of two new species of Terebellidae (Annelida: Polychaeta) representing the first records of the family from deep-sea vents - Reuscher, Michael; Fiege, Dieter; Wehe, Thomas (Journal of the Marine Biological Association of the United Kingdom, 2012)
Terebellomorph polychaetes are reported from hydrothermal vents and cold seeps collected in the Pacific and Atlantic Oceans. Two new species of Terebellidae, Neoamphitrite hydrothermalis sp. nov. and Streblosoma kaia sp. nov., are described from hydrothermal vents of the western Pacific. These are the first terebellid species described from hydrothermal vents. New records from hydrothermal vents and cold seeps and new geographical records are presented for nine additional species belonging to Ampharetidae, Alvinellidae, Terebellidae and Trichobranchidae. A synoptic table with diagnostic characters for all species of the genus Streblosoma Sars, 1872 is provided. Keys for all terebellomorph species currently known from hydrothermal vents and cold seeps, respectively, are included. Additionally the new combination Neoamphitrite pachyderma (Hutchings & Glasby, 1988) comb. nov. is proposed.